A novel piezoelectric wave energy harvester based on cylindrical-conical buoy structure and magnetic coupling. (July 2023) - He, Lipeng; Liu, Renwen; Liu, Xuejin; Zhang, Zheng; Zhang, Limin; Cheng, Guangming
Abstract: Wave energy is a huge renewable energy resource with great potential for development. It can be used to power monitoring sensors on offshore work platforms and bridges. In this paper, a novel piezoelectric wave energy harvester based on cylindrical-conical buoy structure and magnetic coupling (C-PWEH) is proposed. As the wave oscillates up and down, it drives the buoy up and down and forces the piezoelectric patches to deform under magnetic force, thereby collecting the energy from the wave. The efficiency of the wave energy conversion can be improved by optimising the design of the buoy. With magnetic coupling, the low-frequency wave motion can be converted into high-frequency vibrations of the piezoelectric patches thus enabling the device to achieve a better output performance. Experiment findings reveal that the C-PWEH may deliver effective energy production when subjected to wave excitation. When the best matching resistance is 5000Ω, the maximum output power of 41.5 mW can be obtained. Under the optimal experimental parameters, 82 LEDs can be illuminated and power storage tests are performed using capacitors, further demonstrating the feasibility of the C-PWEH powering some low-power sensors.